Metabolic enzymes expressed by cancer cells impact the immune infiltrate. (3rd June 2019) - Stoll, Gautier; Kremer, Margerie; Bloy, Normal; Joseph, Adrien; Castedo, Maria; Meurice, Guillaume; Klein, Christophe; Galluzzi, Lorenzo; Michels, Judith; Kroemer, Guido
ABSTRACT: The expression of two metabolic enzymes, i.e ., aldehyde dehydrogenase 7 family, member A1 (ALDH7A1) and lipase C, hepatic type (LIPC) by malignant cells, has been measured by immunohistochemical methods in non-small cell lung carcinoma (NSCLC) biopsies, and has been attributed negative and positive prognostic value, respectively. Here, we demonstrate that the protein levels of ALDH7A1 and LIPC correlate with the levels of the corresponding mRNAs. Bioinformatic analyses of gene expression data from 4921 cancer patients revealed that the expression of LIPC positively correlates with abundant tumor infiltration by myeloid and lymphoid cells in NSCLC, breast carcinoma, colorectal cancer and melanoma samples. In contrast, high levels of ALDH7A1 were associated with a paucity of immune effectors within the tumor bed. These data reinforce the notion that the metabolism of cancer cells has a major impact on immune and inflammatory processes in the tumor microenvironment, pointing to hitherto unsuspected intersections between oncometabolism and immunometabolism.